Exploration of species diversity and vegetation pattern in temperate conifer forests along altitudinal gradients in the Western Himalayas - Hashim, Muhammad; Bushra, Eamon; Dasti, Altaf Ahmad; Abbasi, Asim; Ali, Hayssam M.; Maqsood, Sumaira; Farooq, Taimoor Hassan; Aslam, Asad; Abbas, Zaheer; Khan, Muhammad Tajammal (Frontiers in Forests and Global Change, 2023)
The moist temperate forests extend along the whole length of outer ranges of Himalaya between the subtropical pine forests and sub-alpine timberline formation with a rainfall from 400 mm to 800 mm. The altitudinal range is from 1500 m to 3000 m. The floristic variation in these Himalayan forests is poorly understood especially in the study area. Species composition may be either unpredictable or it may correspond to environmental heterogeneity. Vegetation from 144 stands in between 2000 – 2700 m altitude was sampled. Soil samples were collected to document edaphic conditions. Soils were physically and chemically analyzed. Ordination (DECORANA) and classificatory techniques were used to analyze the vegetation data. No clear disjunct vegetation patterns emerged from these analyses. The major axes brought out by the ordination were related to altitude and although it is possible to relate the units of classification to broad soil types. Soil chemical properties, litter cover and rockiness were significantly associated with the vegetation variation along an altitudinal gradient. The application of classification to the ordination allowed the interpretations of the vegetation variation in terms of topography and predictable climatic factors such as rainfall, wind speed and extent of snow accumulation. The vegetation patterns revealed have been discussed in relation to the general problem of plant community definition in continuous forest type. Our results demonstrate the overlapping rather than clearly discrete boundaries between the vegetation types and species distributions. This overlapping nature of the vegetation types are discussed in terms of overlapping environmental preferences of the species. Our results are consistent with notion that species separate edaphically and landscape scale within the uniform looking forest. This view maintains that differences in soil within the forest are distinct enough to favor different species, and thus create numerous floristically differentiated forest patches along the altitudinal gradients. The findings that non obvious but distinct floristic and edaphic variation exist within the Himalayan moist temperate forests at the landscape scale have important practical implications for forest management. In biodiversity conservation a high degree of habitat heterogeneity implies an increased need for wide-scale information on species distribution and endemism patterns to better assess where the different habitats are, which species they harbor, and where conservation efforts should be concentrated. The overlapping nature of vegetation types and hazy boundaries of the plant communities implies that plant ecologists must continue to attempt the difficult definition of hazy boundaries.